Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve for [tex]\( y' \)[/tex] and find the slope of the tangent line at the point [tex]\((2, 2)\)[/tex] for the given equation
[tex]\[ \sqrt{12 + y^2} - x^3 + 4 = 0, \][/tex]
follow these steps:
### Step 1: Implicit Differentiation
Differentiate both sides of the equation with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} - x^3 + 4 \right) = \frac{d}{dx}(0). \][/tex]
The left-hand side simplifies using the chain rule.
1. For the term [tex]\( \sqrt{12 + y^2} \)[/tex]:
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} \right) = \frac{1}{2\sqrt{12 + y^2}} \cdot \frac{d}{dx}(12 + y^2) = \frac{1}{2\sqrt{12 + y^2}} \cdot 2y \cdot \frac{dy}{dx}. \][/tex]
Therefore,
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} \right) = \frac{y}{\sqrt{12 + y^2}} \cdot y'. \][/tex]
2. For the term [tex]\( -x^3 \)[/tex]:
[tex]\[ \frac{d}{dx} \left( -x^3 \right) = -3x^2. \][/tex]
3. The term [tex]\( +4 \)[/tex] is a constant, so its derivative is [tex]\( 0 \)[/tex].
Putting it all together, we have:
[tex]\[ \frac{y}{\sqrt{12 + y^2}} \cdot y' - 3x^2 = 0. \][/tex]
### Step 2: Solve for [tex]\( y' \)[/tex]
To isolate [tex]\( y' \)[/tex]:
[tex]\[ \frac{y}{\sqrt{12 + y^2}} \cdot y' = 3x^2. \][/tex]
[tex]\[ y' = \frac{3x^2 \sqrt{12 + y^2}}{y}. \][/tex]
### Step 3: Find [tex]\( y' \)[/tex] at the Point [tex]\( (2, 2) \)[/tex]
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 2 \)[/tex] into the equation for [tex]\( y' \)[/tex]:
[tex]\[ y' = \frac{3(2)^2 \sqrt{12 + (2)^2}}{2}. \][/tex]
Calculate each part:
[tex]\[ (2)^2 = 4, \][/tex]
[tex]\[ 12 + (2)^2 = 12 + 4 = 16, \][/tex]
[tex]\[ \sqrt{16} = 4. \][/tex]
Now substitute back:
[tex]\[ y' = \frac{3 \cdot 4 \cdot 4}{2} = \frac{48}{2} = 24. \][/tex]
### Summary
Therefore, the derivative [tex]\( y' \)[/tex] in general form is:
[tex]\[ y' = \frac{3x^2 \sqrt{12 + y^2}}{y}, \][/tex]
and at the point [tex]\( (2, 2) \)[/tex], the value of [tex]\( y' \)[/tex] (the slope of the tangent line) is:
[tex]\[ \left.y^{\prime}\right|_{(2, 2)} = 24. \][/tex]
So,
[tex]\[ \begin{array}{l} y^{\prime}=\frac{3x^2 \sqrt{12 + y^2}}{y} \\ \left.y^{\prime}\right|_{(2,2)}=24 \end{array} \][/tex]
[tex]\[ \sqrt{12 + y^2} - x^3 + 4 = 0, \][/tex]
follow these steps:
### Step 1: Implicit Differentiation
Differentiate both sides of the equation with respect to [tex]\( x \)[/tex]:
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} - x^3 + 4 \right) = \frac{d}{dx}(0). \][/tex]
The left-hand side simplifies using the chain rule.
1. For the term [tex]\( \sqrt{12 + y^2} \)[/tex]:
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} \right) = \frac{1}{2\sqrt{12 + y^2}} \cdot \frac{d}{dx}(12 + y^2) = \frac{1}{2\sqrt{12 + y^2}} \cdot 2y \cdot \frac{dy}{dx}. \][/tex]
Therefore,
[tex]\[ \frac{d}{dx} \left( \sqrt{12 + y^2} \right) = \frac{y}{\sqrt{12 + y^2}} \cdot y'. \][/tex]
2. For the term [tex]\( -x^3 \)[/tex]:
[tex]\[ \frac{d}{dx} \left( -x^3 \right) = -3x^2. \][/tex]
3. The term [tex]\( +4 \)[/tex] is a constant, so its derivative is [tex]\( 0 \)[/tex].
Putting it all together, we have:
[tex]\[ \frac{y}{\sqrt{12 + y^2}} \cdot y' - 3x^2 = 0. \][/tex]
### Step 2: Solve for [tex]\( y' \)[/tex]
To isolate [tex]\( y' \)[/tex]:
[tex]\[ \frac{y}{\sqrt{12 + y^2}} \cdot y' = 3x^2. \][/tex]
[tex]\[ y' = \frac{3x^2 \sqrt{12 + y^2}}{y}. \][/tex]
### Step 3: Find [tex]\( y' \)[/tex] at the Point [tex]\( (2, 2) \)[/tex]
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 2 \)[/tex] into the equation for [tex]\( y' \)[/tex]:
[tex]\[ y' = \frac{3(2)^2 \sqrt{12 + (2)^2}}{2}. \][/tex]
Calculate each part:
[tex]\[ (2)^2 = 4, \][/tex]
[tex]\[ 12 + (2)^2 = 12 + 4 = 16, \][/tex]
[tex]\[ \sqrt{16} = 4. \][/tex]
Now substitute back:
[tex]\[ y' = \frac{3 \cdot 4 \cdot 4}{2} = \frac{48}{2} = 24. \][/tex]
### Summary
Therefore, the derivative [tex]\( y' \)[/tex] in general form is:
[tex]\[ y' = \frac{3x^2 \sqrt{12 + y^2}}{y}, \][/tex]
and at the point [tex]\( (2, 2) \)[/tex], the value of [tex]\( y' \)[/tex] (the slope of the tangent line) is:
[tex]\[ \left.y^{\prime}\right|_{(2, 2)} = 24. \][/tex]
So,
[tex]\[ \begin{array}{l} y^{\prime}=\frac{3x^2 \sqrt{12 + y^2}}{y} \\ \left.y^{\prime}\right|_{(2,2)}=24 \end{array} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.